Påverkas försöksmöss av att bo på olika platser i djurrummet? - Strigner, Pernilla (SLU/Dept. of Animal Environment and Health (until 231231), 2016)
Among the mammals used in research the mouse (Mus musculus) is the most common. Mice used in research are usually kept in rooms where their cages are placed on shelves. It's desirable to exclude factors that could influence the results of the research. Therefor when animals are used in research they should be held as identically as possible to secure the results. It can be difficult to keep mice in completely standardized comditions, for example the lighting or ventilation can vary at different locations in the same room. Animals included in research are closely monitored and the experiment must be approved by an ethics committee before it can begin. The stress that the animals are exposed to in everyday life outside of the experiments is something that many times are overlooked. Prolonged stress can damage their bodies and it can even lead to changes in behavior. Because the animals behavior can change when they are stressed, the research results may be incorrect. The aim of this study was to find out if there were behavioral differences between mice located at different places in the room. The mice were filmed and their behavior were observed at several predetermined periods of time during the day. I also wanted to find out if and how the mice on the different sites reacted when the room was visited by animal technicians. The study included 12 cages that were placed at six different locations in the room. A total of 36 mice were used, 50% were males. The results from this study showed that the mice tended to be more active when they were placed near the door that led in to the room in comparison to other places in the room. There seemed to be no difference when the mice placed in the bottom shelf were compared to the mice placed in the top shelf. The results indicated that the mice whose cages were placed at the bottom of the shelf showed stress behavior in higher frequency compared with mice placed at the top shelve. Activity levels were in most cases lower after a animal technician visited the room. It may be that mice placed near the door became more exposed to the smells, sounds and light from the hallway witch raised their activity level. Mice are sensitive to sudden changes in the light conditions, have well-developed hearing and an excellent sense of smell. When staff or researchers moved in the room and stood in front of the cages placed on the bottom shelf, they hid the lights in the ceiling. This led to a difference in the intensity of light that was visible on the recorded material, witch may be part of the explanation as to why these mice seem to be more stressed. These mice probably got more sight impressions from the room compared to the mice placed on the top shelf. In this study, the mice did not appear to be particularly affected by visits from an animal technician.